2005
DOI: 10.1111/j.1742-7843.2005.pto960109.x
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal Activity of Edelfosine, Miltefosine and Ilmofosine

Abstract: Abstract:The anti-proliferative action of three alkyl-lysophospholipid derivatives, edelfosine (ET-OCH), miltefosine (Hexadecylphosphocholine), and ilmofosine (BM 14.440) has been studied on the promastigotes and amastigotes of Leishmania donovani. The effect of the three drugs has previously been studied, but the action mode was not clearly elucidated. In this study the effect on the intracellular amastigote forms was evaluated by two different methods: the traditional method, counting the amastigotes within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 29 publications
1
27
0
4
Order By: Relevance
“…A detailed comparative study using a single strain of L. donovani suggested that promastigotes and intracellular amastigotes within peritoneal mouse macrophages were comparably susceptible to miltefosine, with a trend toward greater susceptibility of intracellular amastigotes (27). The greater susceptibility of amastigotes may be attributable to increased cytotoxicity within the macrophage, conferred by alkyl-lysophospholipids promoting the death of intracellular parasites either by direct action of the drug or as a secondary effect on host cells as oxidative burst or production of reactive-oxygen metabolites (28). In contrast to other stud- ies, our study included miltefosine-susceptible and -resistant controls that provided internal references for the interpretation of effective concentrations and reduction of parasite burden.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed comparative study using a single strain of L. donovani suggested that promastigotes and intracellular amastigotes within peritoneal mouse macrophages were comparably susceptible to miltefosine, with a trend toward greater susceptibility of intracellular amastigotes (27). The greater susceptibility of amastigotes may be attributable to increased cytotoxicity within the macrophage, conferred by alkyl-lysophospholipids promoting the death of intracellular parasites either by direct action of the drug or as a secondary effect on host cells as oxidative burst or production of reactive-oxygen metabolites (28). In contrast to other stud- ies, our study included miltefosine-susceptible and -resistant controls that provided internal references for the interpretation of effective concentrations and reduction of parasite burden.…”
Section: Discussionmentioning
confidence: 99%
“…Other alkylphospholipids such as edelfosine, ilmofosine and perifosine have been shown to display antiparasitic activity against Leishmania spp in vitro (Escobar et al 2002, Azzouz et al 2005. Perifosine and miltefosine exhibited a similar activity against L. amazonensis in vitro, whereas edelfosine showed the lowest activity.…”
mentioning
confidence: 94%
“…obs.). As these data indicate that miltefosine is as effective, in vitro, against C. parvum as against Leishmania donovani (Azzouz et al, 2005), it was hoped that the drug would have similar in-vivo efficacy against the two species of parasite.…”
mentioning
confidence: 99%